Preoperative and intraoperative factors contributing to patient satisfaction after bi-cruciate stabilized total knee arthroplasty. (20th August 2021) - Inui, Hiroshi; Taketomi, Shuji; Yamagami, Ryota; Kono, Kenichi; Kawaguchi, Kohei; Tanaka, Sakae
Background: One of the causes of dissatisfaction following total knee arthroplasty (TKA) is abnormal knee kinematics. A newly designed bi-cruciate stabilized (BCS) TKA system has been developed to produce close-to-normal kinematics because of its anatomic tibiofemoral articular geometry and cam-post mechanism. Although BCS TKA is expected to improve patient satisfaction, no reports have described the appropriate technique or soft tissue handling required to achieve excellent satisfaction with BCS TKA. This study is to identify preoperative and intraoperative predictors of patient satisfaction after BCS TKA. Methods: Altogether, we studied 113 knees with primary varus knee osteoarthritis that underwent BCS TKA with a navigation system. Preoperative parameters including Knee Society Score and patient-reported scores [the Knee injury and Osteoarthritis Outcome Score (KOOS)] and intraoperative parameters including coronal, sagittal and axial alignment and joint laxity in each compartment that affected patient satisfaction was evaluated. Satisfaction score was evaluated with use of the 2011 Knee Society Scoring system. The multivariate regression analysis included age and preoperative and intraoperative parameters that correlated with satisfaction scores in the univariate analysis ( P < 0.05). Results: The mean satisfaction score was 28.2 ± 6.1. Multivariate regression analysis showed that the predictors of patient satisfaction were a preoperative high KOOS score for activities of daily living ( P < 0.001), male sex ( P = 0.005), older age ( P = 0.027), and minimal medial joint laxity during flexion ( P = 0.031). Conclusion: When performing BCS TKA, surgeons should pay attention to maintaining proper stability of the medial compartment, especially during flexion.